3
$\begingroup$

I'm trying to evaluate this sum

$$\sum_{n=1}^{\infty}\sum_{k=n}^{\infty}\frac{1}{(n^2+n-1)(k^2+k-1)}$$

I have no idea how to deal with it.

With one sum I can, with partial-fraction decomposition, express it as a function of Digamma function and I stuck there.

$\endgroup$
  • $\begingroup$ Would you know how to deal with just one of the sums? $\endgroup$ – quid May 28 '15 at 16:30
  • 1
    $\begingroup$ with one sum I can, with partial-fraction decomposition, express it as a function of Digamma function and I stuck there. $\endgroup$ – christopher May 28 '15 at 16:35
  • $\begingroup$ I get $$\frac{\pi^2}{10}(1 + 2\cot(\pi\phi)^2) - \frac{4\pi}{5\sqrt{5}}\cot(\pi\phi)\\ \approx 1.722350683738703522582755688460702489148238113214047788297391... $$ using the breakdown appeared in Thomas answer. $\endgroup$ – achille hui May 28 '15 at 17:24
5
$\begingroup$

Suggesting too long for a comment:

When $f(n)$ is a positive function with $\sum_1^\infty f(n)$ converging: $$\left(\sum_{n=1}^\infty f(n)\right)^2=\sum_{n=1}^{\infty}\sum_{k=1}^\infty f(n)f(k)=2\sum_{n=1}^\infty \sum_{k=n}^{\infty} f(n)f(k) - \sum_{n=1}^{\infty}f(n)^2$$

with $f(n) = \frac{1}{n^2+n-1}$

Then the sum you are looking for is:

$$\frac12\left(\left(\sum_{n=1}^\infty \frac{1}{n^2+n-1}\right)^2 +\sum_{n=1}^\infty \frac{1}{\left(n^2+n-1\right)^2}\right)$$

$\endgroup$
3
$\begingroup$

As already pointed by the other answers, we just have to compute: $$ S_1=\sum_{n\geq 1}\frac{1}{n^2+n-1},\qquad S_2=\sum_{n\geq 1}\frac{1}{(n^2+n-1)^2}.\tag{1}$$ and by exploiting the logarithmic derivative of the Weierstrass product for the cosine function we have, for any $\alpha\in\mathbb{R}^+\setminus\mathbb{N}$: $$ \sum_{n\geq 0}\frac{1}{(2n+1)^2-\alpha^2}=\frac{\pi\tan\frac{\pi\alpha}{2}}{4\alpha}\tag{2}$$ as well as: $$ \sum_{n\geq 0}\frac{1}{\left((2n+1)^2-\alpha^2\right)^2}=\frac{\pi ^2 \sec^2\frac{\pi \alpha }{2}}{16\, \alpha ^2}-\frac{\pi\tan\frac{\pi \alpha }{2}}{8\, \alpha ^3}\tag{3}$$ hence it follows that: $$ S_1 = 1+\frac{\pi}{\sqrt{5}}\,\tan\frac{\pi\sqrt{5}}{2}\tag{4} $$ and: $$ S_2 = -1+\frac{\pi^2}{5}\,\sec^2\frac{\pi\sqrt{5}}{2}-\frac{2\pi}{5\sqrt{5}}\,\tan\frac{\pi\sqrt{5}}{2}\tag{5}$$ hence our double series equals:

$$\frac{\pi}{100}\,\sec^2\frac{\pi\sqrt{5}}{2}\left(15\pi-5\pi\cos(\pi\sqrt{5})+8\sqrt{5}\sin(\pi\sqrt{5})\right).\tag{6}$$

$\endgroup$
0
$\begingroup$

Let $p(x)=x^2+x-1$.

Then $$\sum_{n=1}^\infty\sum_{k=n}^\infty\frac1{p(n)p(k)}=\frac12\left[\left(\sum_{n=1}^\infty\frac1{p(n)}\right)^2+\sum_{n=1}^\infty\frac1{p(n)^2}\right]$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.